Tindak Pidana Penistaan Agama Oleh Kelompok Aliran Di Indonesia - Marsudi Utoyo (PRANATA HUKUM, 2012)
Criminal sanctions against the perpetrators of the crime of blasphemy under Article 156, 156a, 157 providing for the offense against religion and public order, in Section 175-177 regulating the violation of religious gatherings, and in Article 178- 181dinamakan Leichenfrevel Grabdelikte and respect for the ceremony kegamaan against those who died (the corpse).The factors that make development of a cult group in Indonesia is, Because seeking the guidance of Allah by way of penance and contemplation. Because there are people who praised excessively, cult, is considered sacred. In the end money, or anything pornographic. Lack of attention to the religious leaders of his people. Grand design of foreign parties to destroy the Muslim creed Indonesia. Someone Personal popularity. Problems of Economics. Not evenly spread of propaganda. Education and Information Flows.